Nutritional characteristics and consumer attitudes towards burgers produced by replacing animal fat with oils obtained from food by-products. (May 2023) - Tarjuelo, L.; Rabadán, A.; Álvarez-Ortí, M.; Pardo-Giménez, A.; Pardo, I.; Pardo, J.E.
Graphical abstract: Highlights: Animal fats were substituted for seed oils obtained from by-products. Reformulated burgers obtained similar values in the sensory analysis. WTP for burgers "with seed oil" label was −0.2831 € per pack. Reference to health benefits of these burgers is recommended to improve acceptance. Abstract: In this study, the oils obtained from melon and pumpkin seeds, considered to be by-products of the food industry, were used to prepare lamb meat burgers. The substitution of each of the emulsified seed oils for animal fat was carried out in three concentrations. The burgers obtained show a reduced percentage of polyunsaturated fatty acids, as well as an increased concentration of vitamin E, with differences depending on the oil emulsion used. To evaluate the acceptance of reformulated burgers, a discrete choice experiment was also used to identify the effects on consumers' purchasing attitudes of using a "with seed oil" label. The results obtained suggest that this label would not lead to greater acceptance of the product, even revealing a negative willingness to pay. In light of the results, the use strategies emphasizing the lower fat content of these burgers ("reduced fat content") or their higher content of polyunsaturated fatty acids is proposed.